DAMPAK MUTUAL RECOGNITION ARRANGEMENT (MRA) ON NURSING SERVICES TERHADAP PROFESI PERAWAT INDONESIA - Yuningsih, Rahmi (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
Nursing in Indonesia began develop into a profession through a National Workshop on Nursing in 1983. Along the times, there is a transfer of nurses, not only work in the country but also abroad. Therefore, ASEAN established MRA on Nursing Services in 2006 as a joint commitment to the ASEAN countries in facilitating the movement of nurses. However, Indonesia, Lao PDR and Viet Nam has not ratified the commitment. On the other hand, many Indonesian nurses are working abroad, especially in ASEAN countries. So the MRA on Nursing Services give impact on nursing Indonesia.This paper would like to analyze the condition of nursing in Indoneia, the regulations related to nursing, main attention the arrangement and impact on nursing services in Indonesia.